2018
DOI: 10.1016/j.ymthe.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of IL13Rα2-Targeted Chimeric Antigen Receptor T Cells for Improved Anti-tumor Efficacy against Glioblastoma

Abstract: T cell immunotherapy is emerging as a powerful strategy to treat cancer and may improve outcomes for patients with glioblastoma (GBM). We have developed a chimeric antigen receptor (CAR) T cell immunotherapy targeting IL-13 receptor α2 (IL13Rα2) for the treatment of GBM. Here, we describe the optimization of IL13Rα2-targeted CAR T cells, including the design of a 4-1BB (CD137) co-stimulatory CAR (IL13BBζ) and a manufacturing platform using enriched central memory T cells. Utilizing orthotopic human GBM models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
237
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(262 citation statements)
references
References 52 publications
(83 reference statements)
5
237
0
Order By: Relevance
“…The patient had an impressive clinical response with complete regression of all intracranial and spinal tumours that lasted for 7.5 months 122 . Strategies to optimize IL-13Rα2-targeted strategies include designing a second-generation 4-1BB co-stimulatory domain-containing CAR product using enriched central memory T cells; in orthotopic glioblastoma models, this product was effective irrespective of corticosteroid treatment (a mainstay of glioblastoma therapy) and had higher efficacy with intraventricular infusions than intravenous delivery (and perhaps also than intratumour administration in the multifocal disease setting) 161 . Anti-GD2 CAR T cell therapy for histone H3 lysine 27-methylated (H3K27me) diffuse midline gliomas, a uniformly fatal type of paediatric CNS tumour, is another promising approach 162 .…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 99%
“…The patient had an impressive clinical response with complete regression of all intracranial and spinal tumours that lasted for 7.5 months 122 . Strategies to optimize IL-13Rα2-targeted strategies include designing a second-generation 4-1BB co-stimulatory domain-containing CAR product using enriched central memory T cells; in orthotopic glioblastoma models, this product was effective irrespective of corticosteroid treatment (a mainstay of glioblastoma therapy) and had higher efficacy with intraventricular infusions than intravenous delivery (and perhaps also than intratumour administration in the multifocal disease setting) 161 . Anti-GD2 CAR T cell therapy for histone H3 lysine 27-methylated (H3K27me) diffuse midline gliomas, a uniformly fatal type of paediatric CNS tumour, is another promising approach 162 .…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 99%
“…36 Follow-up animal studies show that IL-13Ra2-CAR-T cell therapy could be combined with dexamethasone without losing efficacy. 43 These results indicate that CAR-T cell effector activity is surprisingly robust, and may even argue against priming or re-priming effects, which can be perturbed by concomitant glucocorticoid therapy. 94 …”
Section: Possibility Of Car-t Cell Induction Of Endogenous Antitumormentioning
confidence: 95%
“…Drawing from work on cytotoxin‐conjugated IL‐13 that defined mutations which increased the specificity of IL‐13 for IL13Rα2 over the more ubiquitously expressed IL13Rα1/IL‐4Rα complex, an E13Y site‐directed mutation was introduced in IL‐13 . In vitro studies showed that CAR T cells were specific to glioma cells, and consistent with the different affinities of the IL‐13(E13Y) mutein for IL‐13 receptor forms, the engineered T cell activity was observed only against cell lines expressing IL13Rα2 . First‐generation IL13Rα2‐targeted CARs, termed IL13‐zetakine, demonstrated anti‐glioma activity in vitro and in vivo in mice, and second‐generation CAR designs with the inclusion of a 4‐1BB costimulatory domain and an optimized spacer domain improved anti‐tumor potency more than 10‐fold against human GBM xenografts …”
Section: Initial Clinical Experience With Car T Cell Therapy For Gbmmentioning
confidence: 99%